The Relationship between The Physical Fitness and Injuries among the Participants of Basic Air Borne Course - Naprasith, Kasinpiti; Rattananupong, Thanapoom; Jiamjarasrangsi, Wiroj (Journal of The Royal Thai Army Nurses, 2022)
The Objective of this study was to investigate the association between baseline physical fitness level and military static-line parachute injuries in basic airborne trainees of the Special warfare school. A prospective cohort study was conducted among 1,375 military personnel who attended the airborne training program of the Royal Thai Army during 2020. Data about 5 physical fitness tests (2-mile running, 2-minute sit up and push up, pull up, and 100-meter swimming), personal demographics and health histories were collected at baseline, while the occurrence of static-line parachute injuries were observed during five rounds of parachute jump after the ground training. Associations between baseline physical fitness tests and subsequent parachute injury were determined by analyzing Multi-level Poisson Regression and using the Incidence Rate Ratio (IRR) and 95% confidence interval (95%CI) as the risk measure. Result showed that the incidence rate of parachute injury was 34.40 per 1,000 jumps (95%CI: 30.16-39.24). Lower level of 2-mile running capacity was significantly related to the injury [Adjusted IRR (95%CI): 1.75 (1.52-2.00)]. Conclusion, Baseline running fitness level associate with military static-line parachute injuries in basic airborne trainees.